PENGARUH KETAHANMALANGAN DAN KOMUNIKASI INTERPERSONAL TERHADAP ETOS KERJA GURU SEKOLAH DASAR SWASTA DI KECAMATAN CILANDAK JAKARTA SELATAN - Irenne Putren (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
Research conducted has proven that there is an influence of Adversity Quotient and interpersonal communication on the work ethic of private elementary school teachers in Cilandak sub-district, South Jakarta. The research used is research with survey methods and data collection with questionnaires. It can be seen from the result that there is a positive direct effect on each variable. Research shows that the level of resilience to adversity has a positive influence on the work ethic of private elementary school teachers in Cilandak District, South Jakarta. This means that teachers who have a higher level of resilience tend to have a stronger work ethic. The research results also show that interpersonal communication has an important role in influencing teacher work ethic. Teachers who are able to communicate effectively with fellow teachers, students and other related parties tend to have a better work ethic.